Analysing fatty acid profiles and quality indices of different puffer fish species of east Malaysia waters - Samsur, Mohamad (Bioflux, 2024)
Abstract. Despite containing tetrodotoxin, which renders puffer fish inedible and often classifies them as trash fish, these species possess valuable fatty acids, specifically omega-3 fatty acids, which are associated with substantial health benefits. In the present study, the liver and muscles of five distinct puffer fish species namely Xenopterus naritus, Diodon hystrix, Diodon holocanthus, Lactoria cornuta, and Rhynchostracion nasus were examined for their fatty acid content, physicochemical properties, composition, and quality indices. Fatty acids extraction from puffer fish tissues was performed using the cooking-pressing technique, and physicochemical properties of the extracted lipids were determined using the standard AOCS official method. In the liver, fatty acids were between 21.10 and 27.50%, but they were much lower in the muscles, between 0.50 and 1.30%. A comprehensive analysis using gas chromatography identified a total of 22 distinct fatty acids. Saturated fatty acids (SFAs), monounsaturated fatty acids (MUFAs), and polyunsaturated fatty acids (PUFAs) levels in the liver were determined to be 31.52-35.43%, 27.5-37.87%, and 14.63-21.95%, respectively. Muscle, on the other hand, had SFA, MUFA, and PUFA contents of 16.67-19.16%, 24.23-21.00%, and 5.4-12.11%, respectively. The lipid from R. nasus, both from its liver and muscle, exhibited the most beneficial fatty acid profile due to its highest PUFA/SFA and EPA+DHA levels, along with the lowest omega-6/omega-3 ratio. All studied species had values of atherogenic (IA) and thrombogenic (IT) indices lower than 1. X. naritus showed the lowest free fatty acid (FFA) and acid value (AV) levels in both its liver and muscle. D. hystrix showed the highest PV and IV values, while R. nasus had the highest SV value. This study highlights the significance of puffer fish as a potential source of valuable fatty acids, particularly omega-3 fatty acids, offering essential health benefits and nutritional value. Key Words: fatty acid profiles, quality indices, puffer fish lipid, omega-3, polyunsaturated fatty acid.